Lyapunov-Schmidt Method in Bifurcation Solutions of Nonlinear Fourth Order Differential Equation - M.J. Mohammed (مجلة علوم ذي قار, 2019)
this paper studied the bifurcation solutions of elastic beams equation by using Lyapunov-Schmidt method. The bifurcation equation corresponding to the elastic beams equation has been found. Also, the Discriminant set (bifurcation set) of the elastic beams equation has been found for some values of parameters.